The interiority of proximity between nature and arhitecture in contemporary and tropically context with cases studies - Budi Pradono (ARTEKS : Jurnal Teknik Arsitektur, 2019)
The interiority of buildings in tropical countries requires specific characteristics unlike those in countries with four distinct seasons. Buildings in non-tropical climates must protect their inhabitants from extreme weather, meaning that the architecture’s connection with nature is necessarily limited by a boundary which can withstand extreme climatic differences. In tropical countries, on the other hand, the temperature does not fluctuate much throughout the year, so the temperature difference between seasons is not extreme. This characteristic is reflected in traditional Nusantara architecture, which incorporates a breathable wall so that free winds come in, reducing heat. The roof is tilted or saddled-shaped to keep rain water away from the building. The architecture uses organic materials and includes terraces for dialogue with nature. Modern Indonesian architecture, however, particularly in large cities, is mostly closed off, severely limiting the interaction with nature. Since the advent of air conditioning (AC) technology during the 1980’s, architecture has changed to seal the boundaries of the building. Advances in information technology such as Internet and smartphones have made for further changes to architecture in the area; some functional spaces are being discarded, while others are expanded. The relationship between architecture and nature is now constrained by impenetrable materials such as brick, concrete and glass, as opposed to the more traditional, permeable boundary. In contrast to this trend, modern Indonesian society is tempted to form a closer relationship with nature. This paper examines how a relationship between nature and the interior of buildings may be accommodated again, presenting some existing projects by several architects from Europe and Asian countries—including the authors’ own work—as case studies. © 2019 Budi Pradono